BASES OF PUBLIC POLICY FORMATION DIRECTED AT ENSURING BUDGET SECURITY - S. Onishchenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In the article the priorities and public policies that can improve the safety level of the budget of Ukraine have been grounded. Attention on the problems of imbalance and deficiency trends accumulation of public debt has been focused. The detailed analysis of the budget deficit of the European community to further research the main problems of fiscal security has been carried out. The formation of the concept of budget policy should include long-term and medium-term priorities of the state priorities areas have been concluded. Budget policy on public debt must deal with interrelated issues of debt bondage and effective use of public credit, promote economic growth with respect safe level and structure of public debt have been emphasized by author. Debt policy as part of fiscal policy under certain conditions can be a powerful tool to intensify investment and innovation processes in society, promote economic and social development. The reorientation of fiscal policy to address current problems through debt and use it as the basis of investment and innovation development provides an effective public debt management is designed to reduce state budget expenditures on its servicing and repayment, optimizing the scope and structure of debt according to economic growth. The role of debt policy in modern terms increases is clearly subordinate to and consistent with long-term goals and priorities of fiscal policy. There is an urgent development and implementation of effective mechanisms for investing borrowed resources, increasing the efficiency of public investment, including the improvement of organizational, financial, legal and controls. Strategically budget security guarantees only competitive economy, which can be constructed only by recovery and accelerated development of promising sectors of the national economy in the presence of a balanced budget policy. Now there is a tendency to implement only measures to stabilize the political and socio-economic situation in Ukraine has been instead.